Teacher Preparation for Inclusive Education: A Major Concern for India in New Times - Gartia, Radhakanta; Sharma, Sushama (JOURNAL OF INDIAN EDUCATION, 2012)
Fifteen to twenty years ago, regular education teachers had little or no preparation about to educate students with disabilities (D’ Anzola and Giordano, 2006). In recent years, the movement of inclusion to include students with disabilities in regular education settings has reached to mass number of teachers and teacher educated and now it is also creating space in the communities. United Nations Convention on the Rights of the Child in 1989 embodied the human rights for students with disabilities, stating that students with disabilities didn’t want their future decided by others or limited according to their disabilities. They have the right to receive an education to develop their skills.